Frequency and Costs of Out-of-Network Bills for Outpatient Laboratory Services Among Privately Insured Patients - Sen, Aditi P. (JAMA Intern Med, 2021)
IMPORTANCE: Patients may be unaware of which laboratory is processing their clinical tests, limiting their ability to choose an in-network laboratory. Out-of-network laboratory services could increase patients’ out-of-pocket costs and their reluctance to obtain necessary tests. OBJECTIVE: To evaluate the frequency and cost of out-of-network bills for outpatient laboratory services compared with other services. DESIGN, SETTING, AND PARTICIPANTS: This retrospective cohort study of claims data from the Truven MarketScan Commercial Claims database evaluated claims from 3 946 210 individuals (30.5% of the total) in the MarketScan database who were continually enrolled in health maintenance organization plans, preferred provider organization plans, exclusive provider organization plans, or consumer-driven health plans/high-deductible health plans with at least 1 outpatient clinical laboratory service in 2018. Outpatient laboratory services occurred in independent laboratories, physician offices, and outpatient centers. Laboratory bills from January 1, 2010, to December 31, 2018, were studied. EXPOSURES: Receipt and cost of outpatient laboratory service. MAIN OUTCOMES AND MEASURES: The primary outcome was the proportion of outpatient laboratory services billed as out of network. The secondary outcome was the total potential out-of-pocket cost associated with the out-of-network bill, the sum of observed cost sharing, and the potential balance bill. RESULTS: Of the 12 958 130 in the total sample, 30.5% (3 946 210) had a laboratory test, of whom 5.9% received an out-of-network laboratory test. In comparison, 7.1% of the total sample had an emergency department visit, of whom 4.9% had a service billed as out of network, and 1.6% had an inpatient anesthesiology service, of whom 3.4% had an out-of-network service. Observed out-of-pocket spending was $24.59 higher for an out-of-network laboratory service than an in-network laboratory service. In addition, patients with an out-of-network laboratory service may receive an additional balance bill from the laboratory service; the estimated mean balance bill was $80.63. For the most common laboratory services, the total potential out-of-pocket cost associated with an out-of-network bill ranged from $15.68 for venipuncture to $88.09 for lipid panel but was as high as $303.18 for a drug screening test. CONCLUSIONS AND RELEVANCE: In this cohort study, out-of-network laboratory services were 5 times more common than out-of-network emergency department visits and 34 times more common than out-of-network anesthesiology services. It is important for patients that consumer protections against out-of-network bills apply to laboratory services.